Inquisitorial Culture and the False Oralities - André Rocha Sampaio; Marcos Eugênio Vieira Melo (Revista Brasileira de Direito Processual Penal, 2017)
The purpose of this article is to demonstrate the necessity of orality to overcome the insufficiency of measures that concerns the very legal reforms to modify the inquisitorial culture that afflicts us from our matrix. For this, we have used the hypothesis that the orality found in the Brazilian penal process model is of a low intensity, weakened by the authoritarian logic that crosses our penal process dynamics from the outside. Various texts of national and foreign criminal proceduralists were used, mainly those related to the need to unveil the illusion of the "mixed system", the need for the right of confrontation and the restoration of orality. It was hypothesized that an orality in the strong sense cannot be dissociated from the judicial immediacy and, by remedying such deficiency, the dialectical structure of the process could be better evidenced.